(untitled) (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. Sulla nozione di religione, confessione, setta - 2. La Chiesa di Scientology e il suo inquadramento - 3. Problematiche giurisprudenziali nel riconoscimento di Scientology - 4. La configurazione del reati di associazione per delinquere - 5. Il plagio e l’abus de faiblesse - 6. I movimenti “anti-sette”. Considerazioni conclusive. Scientology. Religious narrative and legal rules ABSTRACT: Scientology is an exemplary case, in the definition of "religious confession", both because it is a movement of rupture with respect to the common religious feeling, and because its recognition as confession has taken place, in Italy, following a process that developed, with alternating events, for twenty years, until the final judgment of 2000. It is particularly interesting to reflect on the alleged crimes, which are anomalous if they relate to a religious context, but also on similar trials that have taken place in France and, more recently, in Belgium. In addition, it is important to stress that the three judicial procedures examined were also influenced by two important factors, which were not always explicitly stated in the course of the proceedings: the subject of mental manipulation and the action of anti-cult movements in public debate. If in Italy, plagiarism has been decriminalized by a ruling of the Constitutional Court, in France and Belgium laws have recently been introduced against the abuse of weakness in sectarian movements which, however, have not been recalled in the Scientology trials. Very dangerous is, moreover, the public action of the anti cult movements that can act as a sounding board of news not always reliable and that, often, are financed with public money. All these considerations offer interesting insights into the level of democratic secularism and the protection of religious freedom.